2021
DOI: 10.1186/s12931-021-01697-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of sinus microbiota post endoscopic surgery in patients with cystic fibrosis and chronic rhinosinusitis: a pilot study

Abstract: Background Cystic fibrosis is a debilitating, autosomal recessive disease which results in chronic upper and lower airway infection and inflammation. In this study, four adult patients presenting with cystic fibrosis and chronic rhinosinusitis were recruited. Culture and molecular techniques were employed to evaluate changes in microbial profiles, host gene expression and antimicrobial resistance (AMR) in the upper respiratory tract over time. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Our findings share similarities and build upon prior microbiota studies of CF CRS and CF sputum examining diversity and taxonomic drivers of community structure. Consistent with previous adult CF CRS and sputum studies, microbial community diversity was low ( 4 , 5 , 19 , 32 35 ), and communities were frequently dominated by P. aeruginosa or staphylococci ( 4 6 , 35 38 ). Lucas et al recently showed that low diversity was associated with dominance by Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings share similarities and build upon prior microbiota studies of CF CRS and CF sputum examining diversity and taxonomic drivers of community structure. Consistent with previous adult CF CRS and sputum studies, microbial community diversity was low ( 4 , 5 , 19 , 32 35 ), and communities were frequently dominated by P. aeruginosa or staphylococci ( 4 6 , 35 38 ). Lucas et al recently showed that low diversity was associated with dominance by Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 88%
“…can drive low community diversity and that low diversity is associated with worse sinus disease as measured by mLK score. Additionally, a recent longitudinal study of four adults with CF CRS reported marked stability in sinus communities over time ( 38 ), whereas approximately half of our cohort exhibited instability. These inconsistencies between studies could be due to differences in study design (e.g., cohort sizes or cross-sectional versus longitudinal), methodological differences in sequencing or analysis approaches, or potentially differences in the cohorts themselves, all of which were recruited at single, distinct study centers.…”
Section: Discussionmentioning
confidence: 64%
“…[100][101][102] Given the strong correlation between upper and lower airway microbial populations, it could be inferred from these observations that the CF CRS bacterial population is also resistant to change. 103 There is little consensus on the optimal use of antibiotics in CF-related CRS. 104 Nebulized tobramycin 105 and oral What is the effect of long-term systemic antibiotics, particularly nonmacrolides, on CRS outcomes?…”
Section: Special Considerations Cystic Fibrosismentioning
confidence: 99%
“…( 101 103 ) Given the strong correlation between upper and lower airway microbial populations, it could be inferred from these observations that the CF CRS bacterial population is also resistant to change. ( 104 )…”
Section: Special Considerationsmentioning
confidence: 99%
“…6,7 Culture-independent methods studying the microbiome have demonstrated that the sinuses mirror the lower respiratory tract with polymicrobial communities that progressively become dominated by classical CF pathogens with advancing disease. [8][9][10][11][12] PwCF who have undergone lung transplantation are a unique subgroup in whom the airway microbiome is even less understood. Concordance between the pre-and posttransplant sputum microbiome of PwCF suggests the sinuses are a persistent nidus of airways infection.…”
mentioning
confidence: 99%